CONSTRUÇÕES IMAGINÁRIAS NO CONTEXTO DE UM FENÔMENO MUSICAL DE MASSA: O CASO DO CANTOR MICHEL TELÓ - Souza, Maria Tereza Mazziero de (2015)
Study on the imaginary construction process of the female public to consume the products of mass musical phenomenon in Brazil. Based on the case of the success of singer Michel Teló, representative of the sertanejo universitário musical genre, the goal is to. understand the imaginary construction process that permeates the female audience and consumption of Sertanejo Universitário genre, from the singer Michel Teló discourse. This theoretical framework of the field of Cultural Studies dialogues with studies on imaginary and mass music. Discourse analysis, a French line is the methodology used in two instances to test the reflections built with the theoretical basis: a priori, from a participant observation process for an artist show, which will be observed in the interaction between phenomenon and the public at the time of execution of his song Oh, if I catch you!; and henceforth the musicians speech is analyzed by means of interviews in television programs. A questionnaire administered to a sample of the female audience fond of the singer and his songs still contributes to further reflection. Results of this research, is the understanding of prominence of speech content. Thus, the most important is the way in which the singer speaks to his audience through the image he builds around himself.